Gram‐negative bacterial carriage in chronic rhinosinusitis with nasal polyposis is not associated with more severe inflammation. Issue 4 (30th January 2015) - Tabet, Paul; Endam, Leandra Mfuna; Boisvert, Pierre; Boulet, Louis‐Philippe; Desrosiers, Martin
<x xml:space="preserve">Abstract</x> Background We have previously demonstrated that persistent symptoms following functional endoscopic sinus surgery for chronic rhinosinusitis (CRS) is associated with Gram‐negative bacterial carriage. Mechanisms for this remain unknown. We wished to determine whether Gram‐negative carriage in patients with CRS with nasal polyposis is associated with a more severe inflammatory phenomenon. Methods Three hundred and thirty‐seven patients with CRS with nasal polyposis (CRSwNP) previously phenotyped for genetic association studies with questionnaire, serum biomarkers, and endoscopically‐obtained swab cultures were studied. These were separated according to the presence (wGN) or absence (sGN) of Gram‐negative bacterial carriage; demographic parameters and available serum biomarkers (complete blood count [CBC], total immunoglobulin E [IgE]) were then compared. Subgroup analysis for Pseudomonas aeruginosa (GNwPa) and non‐Pseudomonas Gram‐negative bacteria (GNsPs) was performed in order to explore potentially differential roles of these bacteria. Results Gram‐negative bacterial carriage was not associated with a difference in demographic parameters or serum biomarkers. However, P. aeruginosa carriage was associated with a higher self‐reported incidence of asthma (GNwPa 79%, sGN 57%; p = 0.048). Interestingly, serum IgE was increased in the non‐Pseudomonas Gram‐negative population (GNsPs: 338 IU/mL, sGN: 195 IU/mL; p = 0.026). Conclusion CRSwNP patients colonized with Gram‐negative bacteria have a similar pattern of inflammation as assessed by serum biomarkers to those colonized with Gram‐positive ones. Gram‐negative bacteria may contribute to development of a T helper 2 (Th2) phenotype via other mechanisms, possibly via Toll‐like receptor 4 (TLR4)‐mediated interleukin 33 (IL‐33) production. Differences in phenotype associated with Pseudomonas species carriage suggest a different behavior than other Gram‐negative bacteria, supporting their importance as disease modifiers in CRSwNP.